Effects of salbutamol on bronchoconstriction, bronchial hyperresponsiveness, and leucocyte responses induced by platelet activating factor in man. - Chung, K F (1989)
Platelet activating factor, a potent mediator of inflammation, causes a sustained increase in airway responsiveness to methacholine in man and has been implicated in asthma. The effect of the beta 2 agonist salbutamol (200 micrograms by inhalation) on platelet activating factor induced bronchoconstriction and airway hyperresponsiveness was studied in seven normal subjects in a double blind, crossover study. Salbutamol only partially inhibited the platelet activating factor induced fall in partial flow at 30% of vital capacity (Vp30) (mean percentage fall 47.6 (SEM 7.9); p less than 0.001), whereas it completely blocked a similar degree of bronchoconstriction induced by methacholine. Salbutamol did not prevent the accompanying transient flushing and chest irritation and did not affect the transient neutropenia (mean % fall 69.5 (13.6); p less than 0.01) or the rebound neutrophilia (mean % increase 84.7 (24.7); p less than 0.05) that followed platelet activating factor. There was an increase in the airway responsiveness to methacholine following inhalation of platelet activating factor, the maximum mean change being a three fold increase in PC40 (the provocative concentration of methacholine causing a 40% fall in Vp30) on day 3 (p less than 0.01). Salbutamol caused a significant attenuation of this response on day 3 (p less than 0.02) but had no significant effect on days 1 and 7. Thus a therapeutic dose of salbutamol caused partial inhibition of platelet activating factor induced bronchoconstriction and had a minimal effect on the increased bronchial responsiveness following platelet activating factor.